The global distribution of routine and non-routine work - Piotr Lewandowski; Albert Park; Simone Schotte (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Studies of the effects of technology and globalization on employment and inequality commonly assume that occupations are identical around the world in the job tasks they require. To relax this assumption, we develop a regression-based methodology to predict the countryspecific routine task intensity of occupations based on survey data collected in 46 low-, middle-, and high-income countries. We find that within the same occupation jobs in low- and middleincome countries are more routine intensive than in high-income countries. We attribute these differences mainly to lower technology use in less-developed countries. Using the predicted country-specific measures for 87 countries that together employ more than 2.5 billion workers, we find that from 2000 to 2017 the shift away from routine towards non-routine work was much slower in low- and middle-income countries than in the high-income countries, leading to an increasing gap in average routine-task intensity.
Keywords: J21; J23; J24; 330; de-routinization; economic development; global division of labour; task content ofjobs; skills